The Effect of Laser Acupuncture on Spasticity in Children with Spastic Cerebral Palsy - Dian E. Putri; Adiningsih Srilestari; Kemas Abdurrohim; Irawan Mangunatmadja; Luh K. Wahyuni (Medical Association of Pharmacopuncture Institute, 2020)
Background: Spasticity in cerebral palsy is one of the most common disabilities of children in developing countries. Objectives: The objective of this study was to determine the efficacy of laser acupuncture on spasticity in children with spastic cerebral palsy. Methods: This clinical trial was conducted on 60 patients with spastic cerebral palsy at 2 to 10 years. The patients were categorized into two groups: the control group and treatment group. Laser acupuncture was applied on GV20, GV14, LI4, GB34, and LR3 (power 50 mW, 785 nm, 1 Joule, 40 seconds) three times a week for 12 sessions in the treatment group and placebo laser acupuncture on the same points in the control group. The spasticity was measured using the Modified Ashworth Scale before and after complete sessions. Results: The results showed that there was a significant reduction in the Modified Ashworth Scale score in the treatment group compared with the control group (p = 0.003). Conclusions: This study suggest that laser acupuncture on GV20, GV14, LI4, GB34, and LR3 can reduce spasticity for children with spastic cerebral palsy.